NARRATIVE FUTURING: AN EXPERIMENTAL WRITING INQUIRY INTO THE FUTURE IMAGINARIES - Horst, Rachel (Art/Research International)

(untitled) (University of Alberta, 2021)
In this paper I explore the scholarly potential of a narrative futuring methodology for writing-as-becoming within the context of the future imaginary. Through an experimental bricolage of future fiction, theoretical exploration, and personal essay, I attempt to perform a methodology that troubles temporal boundaries and allows me to write my way into the new. I situate this exploratory work within a rich heteroglossia of creative futures and speculative writing that exists both in and outside the academy and informs my narrative futuring praxis. New materialism and post humanism provide the onto-ethico-epistem-ologies for this creative inquiry in which I attempt to entangle myself with rational possibility, absurd potentiality, and poetic virtuality. The future narrative here is neither predictive nor prophetic, but rather is taken up as a mechanism for doing futures-oriented theory; this is a writing-as-reaching into thick assemblages of the not-yet and storying the productive partiality of narrative (non)representation.